Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Pada Pembelajaran Matematika Materi Bangun Ruang Di Kelas VA SDN 176 Pekanbaru - putri, ardilla putri; Siti Quratul Ain (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The aim of the study was to describe students' difficulties in solving word problems in mathematics learning on geometrical material in the VA class of SDN 176 Pekanbaru. This research method is a qualitative research using a case study approach. The results and conclusions consist of three types, namely as follows: First, students' difficulties in understanding the concept where there are still students who think that mathematics is material that is difficult, scary and unpleasant to learn. The teacher's efforts to overcome students' difficulties in understanding this concept namely by providing learning motivation to students and using unique and interesting learning media during the learning process. Second, students' difficulties in using principles where students have difficulty knowing and explaining the types of geometric shapes discussed in story problems, while the efforts made by the teacher in overcoming students difficulties in using principles are developing good attitudes and study habits. Third, difficulties in solving verbal problems where students have difficulty interpreting and understanding the meaning of language and story problem instructions, and difficulties in using formulas to be used, while the teacher effort to overcome student difficulties in solving verbal problems are providing sufficient and repeated practice and teaching multiplication student.